Learning difficulties prediction. (2016) - Stefanidis, Vasileios; Anogianakis, George; Evangelou, Angelos; Poulos, Marios
In this paper we investigate the possibility to predict brain difficulties during a brain procedure. More specifically, during an educational procedure we investigate Neurophysiological (or Electrophysiological) indexes in order to analyse Electroencephalography (EEG) signals and finally identify and predict difficulties in this educational procedure. More specifically we use Global Field Power, an index which reflects the spatial standard deviation of evoked potentials in brain map. Finally we use classification methods to find a proper mathematical model in order to predict these difficulties.